Biochemical Gradients to Generate 3D Heterotypic‐Like Tissues with Isotropic and Anisotropic Architectures. (9th October 2018) - Canadas, Raphaël F.; Ren, Tanchen; Marques, Alexandra P.; Oliveira, Joaquim M.; Reis, Rui L.; Demirci, Utkan
Abstract: Anisotropic 3D tissue interfaces with functional gradients found in nature are replicated in vitro for drug development and tissue engineering. Even though different fabrication techniques, based on material science engineering and microfluidics, are used to generate such microenvironments, mimicking the native tissue gradient is still a challenge. Here, the fabrication of 3D structures are described with linear/random porosity and gradient distribution of hydroxyapatite microparticles which are combined with a gradient of growth factors generated by a dual chamber for the development of heterotypic‐like tissues. The hydroxyapatite gradient is formed by applying a thermal ramp from the first to the second gel layer, and the porous architecture is controlled through ice templating. A 3D osteochondral (OC) tissue model is developed by codifferentiating fat pad adipose‐derived stem cells. Osteogenic and chondrogenic markers expression is spatially controlled, as it occurs in the native osteochondral unit. Additionally, a prevasculature is spatially induced by the perfusion of proangiogenic medium in the bone‐like region, as observed in the native subchondral bone. Thus, in this study, precise spatial control is developed over cell/tissue phenotype and formation of prevasculature which opens up possibilities for the study of complex tissues interfaces, with broader applications in drug testing and regenerative medicine. Abstract : Spatial control over biochemical gradients directs cell phenotype and prevasculature formation, generating heterotypic but integrated tissues. While the gradient of the microparticles in 3D structures is thermally generated along with the control over pore orientation, the gradient of growth factors is controlled by a dual‐chamber dynamic system. Heterotypic tissues are formed and the structure architecture promotes specific cell marker expression.